Coherent Noise Attenuation Using AGORA Filter on 2D Seismic Data in East Diwaniya, South Eastern – Iraq - Ali, Kamal K.; Ibraheem, Reem Kh.; Thabit, Hassan A. (Iraqi Journal of Science, 2019)
Coherent noise such as ground roll and guided wave is present in the seismic line DE21 (East Diwaniya south eastern Iraq) and it obscures seismic signal and degrades from the quality of data. To attenuate the coherent noise from the shot gather and the Stack of the seismic line, AGORA filter was applied in order to obtain the good signal as the hyperbola shape in shot gather and the reflectors will be clearly to interpret it later. It has given good results and the coherent noise was attenuated in high ratio on all the line. The spectrum analysis is confirmed the effectiveness of AGORA filter to attenuate the coherent noise.